2010
DOI: 10.1111/j.1365-2982.2009.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of autonomic nerve stimulation on colorectal motility in rats

Abstract: Background-Several disease processes of the colon and rectum, including constipation and incontinence, have been associated with abnormalities of the autonomic nervous system. However, the autonomic innervation to the colon and rectum are not fully understood. The aims of this study were to investigate the effect of stimulation of vagus nerves, pelvic nerves (PN) and hypogastric nerves (HGN) on colorectal motility in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
(69 reference statements)
6
28
0
Order By: Relevance
“…Our results in guinea pig are similar to in vivo results in the rat, where PN stimulation increased baseline distal colonic motility at least 2-fold and hypogastric nerve stimulation reduced baseline activity, 31 and transection of these nerves resulted in slowed transit in case of PN and accelerated transit after hypogastric nerve damage. 30 Our results also correspond to findings in dogs, where damage to PN branches slowed down colonic transit, inhibited defecation reflex, 9 and resulted in diminished electrical activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results in guinea pig are similar to in vivo results in the rat, where PN stimulation increased baseline distal colonic motility at least 2-fold and hypogastric nerve stimulation reduced baseline activity, 31 and transection of these nerves resulted in slowed transit in case of PN and accelerated transit after hypogastric nerve damage. 30 Our results also correspond to findings in dogs, where damage to PN branches slowed down colonic transit, inhibited defecation reflex, 9 and resulted in diminished electrical activity.…”
Section: Discussionsupporting
confidence: 87%
“…30 Response to parasympathetic nerve stimulation was abolished by muscarinic receptor blockade, while response to sympathetic nerve stimulation was abolished by beta-adrenoreceptor blockade. 31 We also showed that the PN dissection significantly impaired colonic transit and colonic motility in rats. 10,30 Thus, it is likely that extrinsic innervation, rather than intrinsic innervation, plays a major role in regulating colonic peristalsis of the rat colon.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, a small number of intrinsic neurons in the gut of mouse and guinea pig (but not the rat, see Phillips and Powley, 2007) express TH (Li et al, 2004; Qu et al, 2008). Also, it has been suggested that the vagus nerve in the rat reaches the distal colon (De Groat et al, 1996; Gschossmann et al, 2002; Tong et al, 2010), and since a number of vagal sensory neurons express TH (Ichikawa et al, 1991; Kummer et al, 1993; Matsumoto et al, 2003), they could contribute a fraction of TH-IR afferent fibers in the colorectum.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is frequently observed that handling itself without stress loading produces fecal pellet output. The motor activity of the distal colon is mainly regulated by the pelvic nerves, while the proximal and mid-colon are mainly regulated by vagal nerves in rats (Tong et al 2010). The number of fecal pellets expelled is considered to mainly reflect distal colonic motor function (Million et al 2000), while colonic transit measurement is considered to reflect the motor function of the entire colon.…”
Section: Colonic Transit Studymentioning
confidence: 99%